NIAT BELI GEN-Z PADA TRANSPORTASI ONLINE: EFEK HARGA, KEUNIKAN, NEGOSIASI, DAN ORIENTASI - Pandowo, Aditya; Sumakul, Grace (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2024)
The purpose of this study was to identify the factors that influence purchase intention in Generation Z in online transportation. The population in this study were online transportation users in Manado. Using a quantitative approach, a total of 105 respondents were drawn using a purposive sampling technique where the criteria used were users from Generation Z. Primary data was obtained using a questionnaire distributed via Google Forms. The collected data was then analyzed using Smart-PLS 4.0. The test results show that price and uniqueness can significantly affect purchase intention, while orientation and bargaining power do not affect purchase intention. This research contributes to marketers in developing marketing strategies that focus on price and uniqueness as drivers of creating purchase intention in Generation Z consumers.